(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the impact of value orientations on the formation of professional identity of future psychologists. The author has considered the positions of different author concerning this problem. Analyzed the relationship between value orientations and profes slonal identity.